The quack's daughter : a true story about the private life of a victorian college girl - Nettleton, Greta, 1957- (University of Iowa Press, 2014)
Raised in the gritty Mississippi River town of Davenport, Iowa, Cora Keck could have walked straight out of a Susan Glaspell story. When Cora was sent to Vassar College in the fall of 1884, she was a typical unmotivated, newly rich party girl. Her improbable educational opportunity at "the first great educational institution for womankind" turned into an enthralling journey of self-discovery as she struggled to meet the high standards in Vassar's School of Music while trying to shed her reputation as the daughter of a notorious quack and self-made millionaire: Mrs. Dr. Rebecca J. Keck, second
Keywords: Keck, Cora, -- 1865-1921.; Vassar College -- Alumni and alumnae -- Biography.; Keck, Cora, -- 1865-1921; Vassar College; Women -- Education (Higher) -- United States -- History -- 19th century.; Women musicians -- United States -- Biography.; Women physicians -- United States -- Biography.; Davenport (Iowa) -- Biography.; Femmes -- Enseignement supérieur -- États-Unis -- Histoire -- 19e siècle.; Musiciennes -- États-Unis -- Biographies.; Femmes médecins -- États-Unis -- Biographies.; BIOGRAPHY & AUTOBIOGRAPHY -- Educators.; EDUCATION -- Higher.; HISTORY -- United States -- 19th Century.; Universities and colleges -- Alumni and alumnae; Women -- Education (Higher); Women musicians; Women physicians; Iowa -- Davenport; United States; 1800-1899; Biography; Biographies; History; Biographies.